Intravenous Thrombolysis of Occlusion in the Middle Cerebral and Retinal Arteries from Presumed Ventricular Myxoma - Cheung-Ter Ong; Rei-Yeuh Chang (Stroke Research and Treatment)
Background. Although thrombolytic therapy has been shown to be beneficial to stroke patients, the effectiveness of intravenous thrombolysis in ischemic stroke patients with ventricle myxoma is unknown. Case Description. A 22-year-old woman with left hemiplegia was sent to the emergency department at a teaching hospital. The magnetic resonance angiography showed occlusion of the right middle cerebral artery, and the echocardiography showed a mass in the left ventricle. Intravenous recombined tissue plasminogen activator (rt-PA) was administrated, and the postthrombolysis transcranial Doppler exam showed that her right middle cerebral artery was circulative. The patient's condition improved gradually, and no complication was observed up to 16 months of follow-up. Conclusion. Intravenous rt-PA is a reasonable treatment for stroke patients with ventricle myxoma.